2015
DOI: 10.1155/2015/703407
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Clinical Characteristics and Chest Computed Tomography Findings of Pulmonary Cryptococcosis

Abstract: Objective. The aim of this study was to review HIV-negative patients with pulmonary cryptococcosis to analyze the correlations between clinical characteristics and chest computed tomography (CT) findings. Methods. We retrospectively analyzed medical records of 16 HIV-negative patients with pulmonary cryptococcosis diagnosed at our institution, and clinical characteristics of the patients with nodules or masses without ground-glass attenuation (GGA)/consolidation type were compared with those of patients with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
(21 reference statements)
1
14
0
1
Order By: Relevance
“…Previously, pulmonary cryptococcosis was considered to occur mainly in immunocompromised individuals, such as individuals with AIDS, as well as in individuals that underwent organ transplantation or had a hematologic malignancy, and to be rare in immunocompetent patients (4). Recently, it has reported that the incidence of pulmonary cryptococcosis is increasing (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, pulmonary cryptococcosis was considered to occur mainly in immunocompromised individuals, such as individuals with AIDS, as well as in individuals that underwent organ transplantation or had a hematologic malignancy, and to be rare in immunocompetent patients (4). Recently, it has reported that the incidence of pulmonary cryptococcosis is increasing (12).…”
Section: Discussionmentioning
confidence: 99%
“…These two species are genetically associated with each other; however, they differ genotypically, epidemiologically, ecologically, geographically and phenotypically (2,3). Cryptococcus neoformans occurs most frequently in immunocompromised individuals, particularly those with acquired immunodeficiency syndrome (AIDS) or other causes of impaired T cell-mediated immunity, and less frequently infects immunocompetent patients (4). By contrast, Cryptococcus gattii is more likely to infect healthy individuals, and is associated with tropical and subtropical regions (5).…”
Section: Introductionmentioning
confidence: 99%
“…Intrapulmonary metastasis of lung cancer manifests as multiple intrapulmonary nodules or masses with signs on CT including lobulation, irregular margins, spiculation, vascular convergence sign and pleural indentation ( 7 9 ). Pulmonary tuberculosis on CT manifests as multiple intrapulmonary nodules or masses presenting signs including irregular margins, satellite lesions and tree-in-bud sign ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immunocompetent patients tend to present with nodular or lump-shaped lesions that may vary according to differences in the immune system status. 12 The results of laboratory tests for PC tend to be nonspecific. 7,11 In some patients, lesions may appear as shadowy patches that are often misdiagnosed as pneumonia or tuberculosis 7 ; in others, nodular lesions may form granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…If a patient with anemia and thrombocytopenia shows ground-glass attenuation or consolidation in the lung, pulmonary cryptococcosis should be given careful consideration. 12 The results of laboratory tests for PC tend to be nonspecific. However, tests involving blood, sputum, urine, pleural fluid, and bronchoalveolar lavage fluid; pathogenic examinations; and biopsy cultures are instrumental to an accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%